Efektivitas Aromaterapi Lemon Essential Oil terhadap Mual Muntah pada Pasien Post Sectio Caesarea - Dwi Handoyo; Ika Kusuma Wardani; Anita Devi Kusumawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Sectio caesarea (SC) is a labor process in which the baby is removed from a mother's stomach by incision of the abdomen. Complications that often arise are nausea and vomiting. For nonpharmacological therapies include aromatherapy. Lemon aromatherapy has been widely used by women as much as 40% to relieve nausea, vomiting, and 26.5% of them have been reported as an effective way to control the symptoms of nausea, vomiting. Objective : to determine the effect of aromatherapy lemon essential oil nausea vomiting post sectio caesarea patients with spinal anesthesia at RST Slamet Riyadi Surakarta. Research Method : using quantitative research form one group pre-post test design. The study population was all secsio saesarea surgery patients with a sample of 30 respondents. The sampling technique is Purposive Sampling. Results : The effect of lemon essential oil aromatherapy on the response to nausea and vomiting in post-sectio caesarea patients with spinal anesthesia, in postoperative sectio caesarea patients with spinal anesthesia at RST Slamet Riyadi Surakarta (p <0.001 < 0.05) which means Ha is accepted and H0 is rejected.